(untitled) (Journal of Misan Researches, 2020)
Experimentation is an artistic feature used by authors to change the routine of their texts. Some authors took a negative stand against this type of writing thinking that it would spoil the basic artistic nature of writing. The most prominent writer who took experimentation as a tool and style in showing his narrative achievement is Islam Abu Shakeer. He started and continued as an experimentalist in many of his writings, the most important of which are 30 ˃ 43, Obsession, the Negative O, etc. The research deals with this important achievement by examining the subjects of modern approaches. It studies the works with special attention on the writer’s first collection (30 ˃ 43) to discover the core of narration. The collection shows the possibility of writing in putting what is auditory and mental together. It presented worlds and characters that indicate